2011
DOI: 10.1111/j.1745-4565.2011.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Attenuated Total Reflectance Infrared Microspectroscopy to Discriminate Bacillus Spores

Abstract: In the present study, the potential of Fourier‐transform infrared microspectroscopy to differentiate and discriminate Bacillus spp. spores that sporulated in two nonselective media were evaluated. Spore crops of Bacillus subtilis (ATCC 11779), Bacillus thuringiensis (ATCC 13368, ATCC 35866 and ATCC 55177), Bacillus amyloliquefacies (ATCC 496763) and Bacillus stearothermophilus (ATCC 7953) were obtained with Nutrient and Trypticase Soy Agar supplemented with 10 ppm of MnSO4.H2O. Spores were sonicated, washed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The transmittance spectra of the samples were recorded as a function of wavenumber with a resolution of 2 cm À1 at 25°C. Spectra were displayed in terms of transmittance obtained by rationing the single beam spectrum against that of the air background, [22].…”
Section: Fourier Transform Infra-red (Ftir)mentioning
confidence: 99%
“…The transmittance spectra of the samples were recorded as a function of wavenumber with a resolution of 2 cm À1 at 25°C. Spectra were displayed in terms of transmittance obtained by rationing the single beam spectrum against that of the air background, [22].…”
Section: Fourier Transform Infra-red (Ftir)mentioning
confidence: 99%
“…[17][18][19][20][21] This analytical technique is simple, fast and highly specic, and requires minimal sample preparation. ATR-IRMS has been effectively used to detect subtle differences among samples, [22][23][24][25] which indicated that the IRMS technique could deliver a rapid and sensitive alternative to currently used traditional methods.…”
Section: Introductionmentioning
confidence: 99%